CPIA Africa, July 2017 : Assessing Africa's Policies and Institutions - World Bank Group (World Bank, Washington, DC, 2017)
Sub-Saharan Africa faced another challenging year in 2016. Economic activity continued to weaken, amid less favorable terms of trade, slowdown in global growth, and difficult domestic conditions. Output growth decelerated sharply to 1.3 percent, the slowest pace in over two decades and not as stellar as the average annual growth of around 5 percent in the pre-global financial crisis period of 1995–2008. Regional growth in 2016 was insufficient to raise gross domestic product (GDP) per capita, which contracted by 1.3 percent. At the same time, Sub-Saharan Africa's poverty rate remains high: 41 percent of the region's population—nearly 390 million people—were living in extreme poverty in 2013. Weak economic performance threatens gains in poverty reduction, and the region urgently needs to regain momentum on growth and make it more inclusive.